Number of ways to tile a room with $I$-Shaped and $L$-Shaped Tiles

combinatoricspuzzletiling

There is a room of dimensions $2\times n$. You have to tile it using $2$ types of tiles:

  • I-Shaped Tile ($2\times1$)
  • L-Shaped Tile ($2\times1 + 1$)

image

However, you are forbidden to use any tiling where any four corners of the tiles meet.

For example for a $2\times4$ room, the first three will be counted and the last one will not be counted.

Example

My Attempt

If the condition that four corners cannot meet wasn't given, a pretty neat recurrence can be formed.

$$f(n) = f(n-1) + f(n-2) + 2g(n-1)$$
$$g(n) = f(n-2) + g(n-1)$$

with $g(0) = g(1) = 0$ and $f(0) = f(1) = 1$ where $f(n) = $ number of ways of tiling a $2\times n$ rectangle and $g(n)=$ number of ways of tiling a $2\times n$ rectangle with a square missing on top.

Hence, we multiply $g(n-1)$ by $2$ when calculating $f(n)$ because the missing square can be at the top or the bottom.

I am unable to find such a recurrence with the extra given condition.

Best Answer

The variant can be settled by splitting up into three cases:

  • $f_1(n)$, the number of ways to tile a rectangle ending with a flat line,
  • $f_2(n)$, the number of ways to tile a rectangle where two corners meet in the middle,
  • $g(n)$, the number of ways to tile a rectangle where the top right square is missing.

We have $$ f_1(n) = f_1(n-1) + f_2(n-1) + 2 g(n-1) $$ because the last tile of a rectangle ending in a flat line can either be an I tile or an L tile oriented in two ways. We just have $$ f_2(n) = f_1(n-2) $$ since the only way to create an $f_2$-type rectangle is to put down two horizontal dominoes at the end, and just as before, we have $$ g(n) = f_1(n-2) + f_2(n-2) + g(n-1). $$


From here, it's also possible to write down a linear recurrence for just the total $f(n) = f_1(n) + f_2(n)$ in terms of $f(n-1), f(n-2), \dots$. We have $f(n) = f_1(n) + f_2(n) = f_1(n) + f_1(n-2)$, so it's enough to solve for $f_1(n)$. In fact, as a linear combination of $f_1$ and its translate, $f$ will satisfy the same recurrence relation as $f_1$ with different initial conditions.

From $g(n) = f_1(n-2) + f_1(n-4) + g(n-1)$, we get the infinite series $g(n) = f_1(n-2) + f_1(n-3) + 2f_1(n-4) + 2f_1(n-5) + \dotsb$, and this gives us a recurrence \begin{align} f_1(n) &= f_1(n-1) + f_2(n-1) + 2g(n-1) \\ &= f_1(n-1) + f_1(n-3) + 2g(n-1) \\ &= f_1(n-1) + 3f_1(n-3) + 2f_1(n-4) + 4f_1(n-5) + 4f_1(n-6) + \dotsb \\ \end{align} Subtracting $f_1(n-1)$ from $f_1(n)$, we get $$ f_1(n) - f_1(n-1) = \color{red}{(f_1(n-1) + 3f_1(n-3) + 2f_1(n-4) + 4f_1(n-5) + 4f_1(n-6) + \dotsb )} - \color{blue}{(f_1(n-2) + 3f_1(n-4) + 2f_1(n-5) + 4f_1(n-6) + 4f_1(n-7) + \dotsb )} $$ and most of the red terms cancel with blue terms, leaving us with $$ f_1(n) - f_1(n-1) = f_1(n-1) - f_1(n-2) + 3f_1(n-3) - f_1(n-4) + 2f_1(n-5) $$ or $f_1(n) = 2f_1(n-1) - f_1(n-2) + 3f_1(n-3) - f_1(n-4) + 2f_1(n-5)$. As observed earlier, this also means that the recurrence $$f(n) = 2f(n-1) - f(n-2) + 3f(n-3) - f(n-4) + 2f(n-5)$$ holds.


The first few nonzero terms of the sequence are $1, 1, 2, 5, 10, 22, 49, 105, 227, 494, 1071, \dots$, as computed by @PeterKagey in the comments and in the upcoming OEIS listing.